(3CUhd GdfMh YfO fMGI Gdjef aj GdbQfjf GdKGef hGdJGSY GdgLQjjf (B/ s - (3aJM YHOg UGdM eSYO s; (3CMeO eMeO YHO GdYRjR cTc (B: s ((3GdbGgQI (B: s (3aJM YHOg UGdM eSYO (B: s, 2017)
(3cTaJ GdOQGSI Yf TNUjGJ jefjI fMhjI HGQRI aj GdfMh GdYQHj(B: (3CfJLJ ackQG fMhkjG fGVkLG heJWhkQG(B: (3CTgQge GdYdhj hGdegOj hGHf gWjd hGdfLQGfj hGdQUGU hGHf CHj GdbGSe(B: (3hJaQO HYVge HBQGA fMhjI GSgeJ aj Qbj GdOQS GdfMhj hfVLg hJWhQg(B. (3oJYoqO gPg GdOQGSI eMGhdI LGOI dEdbGA GdVhA Ydi GdOQS GdfMhj aj Gdjef hefgL fMGI Gdjef aj JYGedge eY CUhd GdfMh GdeNJdaI ef NdGd cJHge(B: (3aQSeJ UhQI ObjbI dCUhd GdfMh YfOge(B: (3aXgQJ TNUjGJ CUhdjI fMhjI SdcJ dfaSgG efgkLG hCSdhkHG aj bVGjG GdCUhd GdeNJdaI(B: (3hCXgQJ JCKkQG hGVkMG HGdabgGA hGdeJcdejf hGdefGWbI NGUI aj GdYdI GdfMhjI(B. (3hocSQJ GdOQGSI Edi CQHYI aUhd Med GdaUd GdChd GdSeGY(B: (3hGdKGfj GdbjGS(B: (3hGdKGdK GdYdI(B: (3hGdQGHY GdELeGY hCOdI CNQi(B: (3cGdGSJUMGH(B: (3hGdGSJbQGA(B: (3hGdSHQ hGdJbSje(B: (3hGdChdi(B. (3hoUpqOQ GdHMK HebOeI hJegjO(B: (3hCYbH GdaUhd NGJeI hagGQS afjI(B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh GdUQa hGdYQhVs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CUhd GdfMh s; (3GdbQfjf GdKGef hGdJGSY GdgLQjjfs; (3fMGI Gdjef s